Profits, R&D and Innovation: a Model and a Test - Francesco Bogliacino; Mario Pianta (European Commission, Joint Research Centre (JRC), 2010)
In this article we investigate – both conceptually and empirically – the relationship between three interconnected elements of the Schumpeterian “engine of progress”: the ability of industries' R&D efforts to turn out successful innovations; the ability of innovations to lead to high entrepreneurial profits; the commitment of industries to invest profits in further technological efforts. We build a simultaneous three-equation model – with appropriate lags – and we test it at industry level – for 38 manufacturing and service sectors – on eight European countries over two time periods from 1994 to 2006. The results show that the model effectively accounts for the dynamics of European industries. Our main results are that demand and innovation are the key determinants for firm profitability; second that both technology adoption and R&D concur to improve innovative performance; third, that R&D is path dependent and is negatively related to the distance from the frontier. Finally, manufacturing and services show similar behaviour.
Keywords: L6; L8; O31; O33; O52; 330; Profits; R&D; Innovation; System Two Stages Least Squares